Set a thief... (Economist, 2014)
The article discusses microbiomes and a research paper in the journal "Cell" that claims scientist Dr. Mohamed Donia and his colleagues have designed a computer software program that is able to scan DNA databases for genes that look as if they are involved in antibiotic production.